Comprehensive Physiology 1997
DOI: 10.1002/cphy.cp130224
|View full text |Cite
|
Sign up to set email alerts
|

Daily and Seasonal Rhythms

Abstract: The sections in this article are: Daily Rhythms Models and Mechanisms Circadian Pacemaking Systems in Invertebrates Pacemakers in the Arthropod Brain Circadian Pacemakers Outside the Nervous System in Insects Pacemakers in the Gastropod Retina Multioscillator Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 996 publications
0
11
0
Order By: Relevance
“…The seasonal cycles mold the phenology of insects through extreme temperatures, resource availability and competition, affecting population structure, mating, growth and development, among other factors (underWOOd et al, 1997). Even in subtropical regions, seasonal climate changes influence the foraging behavior of bees.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal cycles mold the phenology of insects through extreme temperatures, resource availability and competition, affecting population structure, mating, growth and development, among other factors (underWOOd et al, 1997). Even in subtropical regions, seasonal climate changes influence the foraging behavior of bees.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental lighting protocols have been used to show an important role for the circadian system in photoperiodic time measurement in a number of vertebrates; these include night-breaks (skeleton photoperiods), resonance cycles, and T-cycles (Elliott and Goldman, 1981;Hamner, 1963;King et al, 1997;Kumar and Tewary, 1982;Puchalski and Lynch, 1994;Siopes and Wilson, 1980;Underwood and Hyde, 1990;Underwood et al, 1985Underwood et al, , 1997bWhitsett et al, 1984). Night-break experiments are probably the least useful of the protocols in proving circadian involvement because a positive response to a night-break is compatible with either a circadian-based timing mechanism or an hourglass timing mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a significant role for the circadian system in photoperiodic time measurement in virtually every vertebrate species examined to date (Underwood et al, 1997b). Bünning (1936Bünning ( , 1960 was the first to suggest that an endogenous daily rhythm may be involved in measuring changes in daylength.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One blinded bird was eliminated from analysis, since its peak blood melatonin levels were more than three SD from the group mean. In mammals, the only photic input pathway to the circadian system is via the eyes, and the main circadian pacemaker is located in the SCN (16,31). By contrast, birds possess at least three photic input pathways (the retina, the pineal organ, and extrapineal, extraretinal receptors in the brain), and circadian pacemakers located in the pineal and/or eyes drive circadian oscillators located in the SCN (29,30).…”
Section: Experiments 5: Effects Of the Apsp Protocol On Ocular Melatonmentioning
confidence: 99%